Frontiers in Software Engineering Education Second International Workshop, FISEE 2023, Villebrumier, France, January 23-25, 2023, Invited Papers - Capozucca, Alfredo; Ebersold, Sophie; Bruel, Jean-Michel.; Meyer, Bertrand (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes invited papers from the Second International Workshop on Frontiers in Software Engineering Education, FISEE 2023, which took place at the Château de Villebrumier, France, during January 23-25, 2023. The Editorial and the 8 papers included in this volume were considerably enhanced after the conference and during two different peer-review phases. The contributions cover the main topics of the workshop: education in technology and technology for education; new (and fearless) ideas on education; adjustments in teaching during pandemic: experience reports; models for class development; how to design learning objectives and outcomes; labs and practical sessions: how to conduct them; curriculum development; course design; quality course assessment; long-life studies in education; empirical research in SE education; experiences in starting-up new educational systems; blended education. FISEE 2023 is part of a series of scientific events held at the new LASER center in Villebrumier near Montauban and Toulouse, France.
Keywords: Software engineering; Computer programming; Education -- Data processing; Database management; Computer science; Software Engineering; Programming Techniques; Computers and Education; Database Management; Computer Science Logic and Foundations of Programming